Sistema integrador para la gestión de indicadores de calidad en la facultad de Ciencias de la Ingeniería y Aplicadas, indicador seguimiento Prácticas Preprofesionales. - Chicaiza Toapanta, Jessica Karina (2019)
In the Technical University of Cotopaxi, within the area of Pre-Professional Practices, it is required to automate the different processes, evidencing that at the moment there is not any available software tool that allows carrying out the activities of tutors, coordinators and students, in such a way that this process has been done in IT tools, generating excessive documentation and waste, loss of time. This research aims to provide a computer system that allows the systematization of activities, the management and control of information. For the development of the research, the interview and survey techniques were applied, in order to better understand the problem that has been caused, for which the Agile SCRUM Methodology was used, since it facilitated the development process of software. In order to achieve the aforementioned, the use of the programming language C #, the SQL Server 2012 database, was specified. Finally, it is concluded that with the implementation of this application, processes can be generated faster and reliably, which will reduce time in the delivery of reports and reports.